Design of therapeutic siRNAs for potential application to infection with chikungunya virus - Ahmed Ahsan Adib; Muhammad Manjurul Karim (Heliyon)
Emergence of the Chikungunya virus (CHIKV) is a new threat in the world. The disastrous effect of this virus and the unavailability of specific drugs complicated the control and management of the disease. The development of a siRNA-based drug using multiple computational tools could be a way out as one of its therapeutics. Currently, very few siRNAs against CHIKV have been computationally designed and published. Here, we considered various parts of the CHIKV genome encoding different essential protein-coding genes for designing siRNAs with a view to silencing them, thereby rendering the virus inactive. Seven potential primary siRNAs were constructed, of which, five are hereafter recommended to be used as a therapeutic tool against the virus.